Missense and truncated variants in ERF in individuals with a Noonan-like phenotype without craniosynostosis - Yusuke Goto; Tetsuya Niihori; Seiji Mizuno; Nobuhiko Okamoto; Tsutomu Ogata; Kenji Kurosawa; Hirofumi Ohashi; Yoichi Matsubara; Taiki Abe; Atsuo Kikuchi; Yoko Aoki (Scientific Reports)
Abstract ETS2 repressor factor (ERF) is a member of the ETS family of transcriptional repressors downstream of ERK. Although germline truncated variants in ERF have been identified in individuals with Noonan-like syndrome with or without craniosynostosis, the clinical spectrum of ERF variant-positive individuals and the functional characterization of ERF variants are currently not fully understood. In this study, we identified one missense variant (p.G53R) and two truncating variants in ERF using whole exome sequencing (WES) in three individuals and one truncating variant using Sanger sequencing in one of 81 individuals with suspected Noonan syndrome without any pathogenic variants by targeted analysis in the previous study. Four Individuals with pathogenic ERF variants were diagnosed with Noonan-like syndrome, where craniosynostosis was not evident. Our investigation revealed that wild-type ERF undergoes nuclear-cytoplasmic shift, whereas truncated mutant ERF are predominantly localized in the nucleus. Moreover, R183* and G299Rfs variants lost their ability to repress the proliferation of osteoblast-like cells (MC3T3-E1). A luciferase assay examining the transcriptional activity of RUNX2 binding motifs indicated that the truncated variants were defective in their suppressive function. Further experimentation demonstrated that MC3T3-E1 cells expressing the p.G53R and three truncating variants induced ossification compared to the wild-type. These results suggest that loss-of-function mutations in ERF, which result in reduced ossification suppressor activity in MC3T3-E1 cells, can lead to craniofacial abnormalities in individuals with Noonan syndrome-like symptoms.